A new epoch in assessing fetal heart condition - V. I. Tsibizova; I. I. Averkin; V. O. Bitsadze; A. V. Kozlenok; E. V. Grekhov; T. M. Pervunina; K. V. Petrov; D. O. Saprykina; D. V. Blinov (Акушерство, гинекология и репродукция, 2021)
Assessment of fetal cardiac function is one of the essential components of fetal echocardiography. Functional impairment is associated with a high risk of adverse perinatal outcomes and even antenatal death. Prenatal detection of hemodynamics changes requires immediate prenatal actions to identify the causes and eliminate the consequences that may require conservative treatment, intrauterine surgical treatment, and early delivery in perinatal centers.